Springate Model to Analyze Liquidity, Leverage, and Profitability Ratios Toward Financial Distress - Shafira Ayu Rachmawati; Lenni Yovita; Diana Puspitasari; Fakhmi Zakaria (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study systematically analyses the predictive ability financial ratios have in relation to the emergence of financial distress among non-cyclical companies on the Indonesia Stock Exchange during the period 2020-2023. Secondary data was collected from a sample of 151 secondary data companies listed on the Indonesia Stock Exchange, spanning the years from 2020 to 2023. In order to ascertain the relationship between the independent variables (X1, X2, X3) and the dependent variable, Multiple Linear Regression models are utilised by employing the Eviews calculation application. As a model, the Springate model is employed, which is used to measure financial distress. The financial ratios selected for analysis encompass the liquidity ratio, the leverage ratio, and the profitability ratio. The findings of this study suggest that the profitability ratio exerts a substantial positive effect, or a moderate effect, on the phenomenon of financial distress. In contrast, the liquidity ratio and leverage ratio demonstrate an absence of statistically significant influence on the phenomenon of financial distress. Extensive analysis of the results indicates that financial distress, as measured by Springate, does not exert a substantial influence on the findings obtained from this study. The incorporation of diverse samples and models in subsequent studies is likely to introduce variations into the research outcomes.